DIGITALISASI PUBLIKASI LAPORAN KEUANGAN DAERAH - Hardiningsih, Pancawati; Srimindarti, Caecilia; Jannah, Afifatul; Haryanto, Maria Yosaphat Dedi (Catholic University Musi Charitas, 2021)
Digitalization disclosure is considered capable of reaching all aspects of society and can be accessed at any time. Advances in technology will make all information accessible easily, cheaply, and quickly. This study aims to analyze the influence of government size, accessibility, and audit opinion on the disclosure of digital local government financial reports. Population and research sample are Local Government Financial Statements. Central Java Province, as many as 29 Regency Governments and 6 City Governments for the 2015-2018 Fiscal Year that have been audited by the Supreme Audit Agency. The analysis technique uses multiple regression with the Fixed Effect Model. The results show that all independent variables, namely government size, accessibility, and audit opinion have a positive and significant effect on the disclosure of digital local government financial statements.